PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP MOTIVASI KERJA SERTA DAMPAKNYA TERHADAP KINERJA KARYAWAN (STUDI KASUS DI YOGYA CHICKEN DAERAH ISTIMEWA YOGYAKARTA) - Inayat Hanum Indriati (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2018)
PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP MOTIVASI KERJA SERTA DAMPAKNYA TERHADAP KINERJA KARYAWAN (Studi Kasus di Yogya Chicken Daerah Istimewa Yogyakarta)Inayat Hanum IndriatiUniversitas PGRI YogyakartaKorespondensi : inayathanum10@gmail.comHuman resources are central figures in organizations and companies. Therefore, the existence of human resources within the company must be considered by the leadership or management. The purpose of this study to determine the effect of work environment and compensation on work motivation and its impact on employee performanceThis study uses a sample of employees Restaurant